O processo de implantação da Polícia Comunitária em Mato Grosso - Jesus, Fábio Henriques de (2013)
This study sought to draw a picture of the process of implementation of community policing in Mato Grosso, investigating the factors that made it conducive to the emergence of this form of fighting crime in the state, its peculiarities, forms of integration with the community, forms of action and prospects for the future. Therefore, we sought to study the factors that prevented the emergence of the Police Community in the world a phenomenon closely linked to the movement of construction and expansion of citizenship rights in liberalism in the late nineteenth century, which had great momentum after the second half of the century, the period of the most lavish social achievements of so-called “ welfare state “. Proved the advent of neoliberalism today, with its doctrine of dismantling social rights and reducing the role of the state, because of the crisis that hit welfare states from the mid - 1970s. We sought to draw a panel of Brazilian political conjuncture marked by decades of authoritarian rule, where the welfare state never ceased to be a promise never actually met, and that from the 80s has been undergoing a process of democratization, culminating in the enactment in 1988 of the Federal Constitution, not by chance called “ Citizen Constitution “, resulting in a long process for the expansion of social rights in Brazil and win citizenship. Thus, we sought to know the setting and the nuances that permeated the adoption of community policing in the state of Mato Grosso. With this, we seek to understand the relationships that community movements began to establish with the public security institutions in an attempt to facilitate a change in traditional practices of authoritarianism, clientelism and paternalism, aimed at making more adhesive formulation of public policies to the needs of a society increasingly aware of their role in the political arena.